Analisis Pemikiran Karl Marx Tentang Sosialisme Dalam Perspektif Ekonomi Islam - Dewi Rahmi Fauziah; Nella Yuliantina (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2024)
Karl Marx, a famous philosopher, economist, and political theorist, has made significant contributions to the thought on socialism can be analyzed in the perpsective of Islamic economics, which has unique principles and values. Marx decribed socialism as a step towards a classless society, where ownership and control over economic resources are in the hands of the whole society. This thinking is in line with the basic principles in Islamic economics, which emphasize social justice and fair distribution. In Islamic economics resources must be done with regard to public welfare and minimize social inequality. In conclusion, Karl Marx’s thoughts on socialism can be analyzed in the perspective of Islamic economics, which emphasizes social justice and fair distribution. Although there are fundamental differences between the two, Marx’s thoughts can provide a valuable understanding of social and economic issues relevant to the context of Islamic economics.Keywoard : Socialism, Karl Marx, Islamic Economics